Yttrium oxide buffer layer-based photovoltaic device and preparation method and application thereof
By introducing an yttrium oxide buffer layer into perovskite photovoltaic devices, the stability and efficiency problems caused by ion migration are solved, and higher photoelectric conversion efficiency and thermal stability are achieved.
Patent Information
- Application Number
- CN202411374731.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-24
AI Technical Summary
Organic and inorganic hybrid perovskite photovoltaic materials cause device stability attenuation, electrode corrosion and metal diffusion due to ion migration, which affects photoelectric conversion efficiency and device life.
A buffer layer of yttrium oxide (Y2O3) is introduced between the metal electrode and the charge transport layer, and the buffer layer is prepared in a large area through thermal evaporation technology to inhibit ion migration and promote electron collection.
Effectively improve the stability and optoelectronic conversion efficiency of perovskite solar cells, improve the filling factor and opening voltage, and significantly enhance the thermal stability of the device.
Smart Images

Figure CN119365032A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optoelectronic materials and devices, and specifically relates to an yttrium oxide buffer layer and a preparation method thereof, and applications of photovoltaic devices. Background Art
[0002] Through strategies such as defect passivation, the photoelectric conversion efficiency of organic-inorganic hybrid perovskite solar cells has exceeded 26%. However, since organic-inorganic hybrid perovskite photovoltaic materials are soft lattice crystals, light, bias and thermal stress will cause ion migration in the perovskite body. Ion migration will cause changes in chemical composition within the micrometer scale, including poor component uniformity and the generation of non-radiative recombination centers, which will cause the stability of the device to decay. On the one hand, the mobile ions generated in the perovskite will diffuse into the charge transfer layer and accumulate at the electrode interface. The aggregated ions will corrode the electrode, destroy the integrity of the electrode, and thus destroy the stability of the device. On the other hand, the metal electrode will also diffuse into the charge transfer layer and the perovskite layer, which is also not conducive to the stability of the device. Under actual working conditions, perovskite solar cells need to absorb light energy and generate bias, which inevitably causes ion migration and affects the stability of the device.
[0003] An effective way to solve the above problems is to introduce a buffer layer between the metal electrode and the charge transport layer. The introduction of the buffer layer is of great significance for improving the stability of the device. At the same time, the buffer layer needs to be able to promote the transfer of charges from the transport layer to the electrode, ensuring that the charges in the device can be efficiently collected by the electrode. Summary of the invention
[0004] In order to solve the problem that ion migration affects the stability of the device, the present invention provides a photovoltaic device based on an yttrium oxide (Y2O3) buffer layer, a preparation method thereof, and an application thereof. The yttrium oxide used in the present invention can be prepared on a large scale by thermal evaporation, which is conducive to commercialization.
[0005] The present invention confirms for the first time that yttrium oxide, as a buffer layer, effectively promotes the collection of electron carriers by electrodes, inhibits ion migration, and hinders hole transmission, thereby effectively improving the stability and photoelectric conversion efficiency of perovskite solar cells.
[0006] The technical solution provided by the present invention is as follows: A photovoltaic device based on an yttrium oxide buffer layer and a preparation method and application thereof, comprising the following steps: (1) Preparing an yttrium oxide buffer layer; (1.1) Place metal yttrium (Y) in a vacuum of approximately 4x10 -4 Pa evaporates onto the FTO glass substrate in a vacuum environment to form metallic yttrium; (1.2) The evaporated metallic yttrium is placed in an external environment for natural oxidation to obtain an yttrium oxide buffer layer.
[0007] (2) preparing a tin dioxide transport layer; (2.1) mixing a tin dioxide colloidal solution, deionized water, and hydrogen peroxide, and stirring to obtain a hydrogen peroxide-modified tin dioxide precursor solution; (2.2) Spin-coating a tin dioxide precursor solution modified with hydrogen peroxide onto the yttrium oxide buffer layer, and annealing to obtain a tin dioxide transport layer; (3) Preparation of perovskite light absorbing layer film; (3.1) Dissolve PbI2 in an organic solvent; (3.2) Dissolve the ammonium salt in isopropanol; (3.3) Spin-coat the PbI2 solution on the tin dioxide transport layer, anneal to room temperature, spin-coat the ammonium salt solution on the PbI2 layer, and then anneal in an atmospheric environment to obtain a perovskite light-absorbing layer film; (4) preparing a hole transport layer; (4.1) Dissolve lithium bis(trifluoromethanesulfonyl)imide in acetonitrile; (4.2) Dissolve 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in chlorobenzene, add 4-tert-butylpyridine and acetonitrile solution of lithium bis(trifluoromethanesulfonate), heat and stir to react, and obtain a hole transport layer solution; (4.3) Spin coating the hole transport layer solution onto the perovskite light absorbing layer film to obtain the hole transport layer; the spin coating speed is 3000 rpm and the spin coating time is 20 s; (5) Preparation of top electrode; A top electrode is evaporated on the hole transport layer.
[0008] Furthermore, the tin dioxide precursor solution in step 2.1 is stirred at room temperature for 24 hours to obtain a tin dioxide solution, deionized water, and hydrogen peroxide solution in a volume ratio of 1:4:1.
[0009] Furthermore, in step 2.2, the spin coating speed is 4000 rpm, and the spin coating time is 30 s; the annealing temperature is 150° C., and the annealing time is 30 min.
[0010] Furthermore, in step 3.1, the organic solvent is a mixed solvent of DMF and DMSO, and the volume ratio of the two is 9:1; the dissolution temperature is 60°C, and the stirring time is 24 h.
[0011] Furthermore, the annealing temperature of the PbI2 solution in step 3.3 is 70°C; the concentration of the ammonium salt solution obtained by dissolving the ammonium salt in isopropanol is about 0.76 M, and the ammonium salt includes FAI and MACl; the atmospheric humidity during annealing is about 35%, the annealing temperature is 145°C, and the annealing time is 13 min. The mass ratio of FAI to MACl is 90:16.
[0012] Furthermore, in the step 4.2, the dosage ratio of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, chlorobenzene, 4-tert-butylpyridine and the acetonitrile solution of lithium bis(trifluoromethylsulfonate)imide is 72.3 mg:1 mL:28.8 μL:17.5 μL; the ratio of lithium bis(trifluoromethylsulfonate)imide to acetonitrile in the acetonitrile solution of lithium bis(trifluoromethylsulfonate)imide is 520 mg:1 mL.
[0013] Furthermore, in step 5, the evaporated top electrode is a gold electrode.
[0014] During the preparation process, except for the tin dioxide electron transport layer, which was prepared under open air conditions, the rest, including yttrium oxide, perovskite, hole transport layer and top electrode, were prepared under an inert gas protection atmosphere. In addition, after the hole transport layer was prepared, it needed to be placed in a drying cabinet for oxidation for 48 hours before preparing the top electrode.
[0015] Another object of the present invention is to provide a photovoltaic device prepared by the above method, the photovoltaic device comprising, from bottom to top, a conductive glass substrate, yttrium oxide, a tin dioxide transport layer, a perovskite light absorption layer film, a hole transport layer and a top electrode layer. The yttrium oxide buffer layer is prepared by the following method: evaporating metal yttrium (Y) onto a FTO glass substrate under a vacuum environment to form a metal yttrium layer; placing the evaporated metal yttrium in an external environment for natural oxidation to obtain the yttrium oxide buffer layer.
[0016] The thickness of the yttrium oxide is about 2 nm, the thickness of the tin dioxide transport layer is 30 nm, the thickness of the perovskite light absorption layer film is 900 nm, the thickness of the hole transport layer is 80 nm, and the thickness of the top electrode layer is 80 nm.
[0017] Furthermore, the perovskite light absorbing layer film is an organic-inorganic hybrid perovskite FAPbI3.
[0018] The present invention also provides application of the photovoltaic device in solar cells.
[0019] Beneficial effects of the present invention: 1. The preparation method provided by the present invention is simple, has good repeatability, high uniformity, can be prepared on a large scale, and is conducive to commercial application; the raw materials are easily available and low in cost, which is conducive to reducing the preparation cost; 2. The yttrium oxide buffer layer prepared by the present invention can promote the collection of charges by the electrode, inhibit ion migration, and help improve the stability of the device; 3. The photovoltaic device based on the yttrium oxide buffer layer provided by the present invention effectively improves the photoelectric conversion efficiency of the perovskite solar cell by up to 26%, which is mainly reflected in the improvement of the fill factor and the open circuit voltage, and has great application development potential.
[0020] 4. The photovoltaic device based on the yttrium oxide buffer layer provided by the present invention effectively improves the thermal stability of the perovskite solar cell. After 430 hours of continuous heating at 85°C, it can still maintain 83.7% of the initial efficiency, while the device without yttrium oxide can only maintain 72.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a device structure diagram of a planar perovskite thin film solar cell, where 1-conductive glass substrate, 2-yttrium oxide, 3-tin dioxide transport layer, 4-perovskite light absorption layer film, 5-hole transport layer Spiro-OMeTAD, 6-top electrode; Figure 2 is a performance statistical diagram of the perovskite thin film solar cell prepared in Example 1; Figure 3 is a performance statistical diagram of the perovskite thin film solar cell prepared in Example 2; Figure 4 is a thermal stability diagram of the perovskite thin film solar cell prepared in Example 2; Figure 5 is a performance statistical diagram of the perovskite thin film solar cell prepared in Example 3; Figure 6 is a performance statistical diagram of the perovskite thin film solar cell prepared in Comparative Example 1; Figure 7 This is a thermal stability diagram of the perovskite thin film solar cell prepared in Comparative Example 1. DETAILED DESCRIPTION
[0022] The present invention is further described below in conjunction with embodiment, and this description is only for better illustrating the present invention rather than limiting it. The present invention is not limited to the specific examples and embodiments described herein. Any technician in the art is easy to make further improvements and perfections without departing from the spirit and scope of the present invention, and all fall into protection scope of the present invention. Example 1
[0023] The schematic diagram of the structure of the photovoltaic device based on the yttrium oxide buffer layer in this embodiment is as follows Figure 1As shown, from bottom to top are a conductive glass substrate 1, an yttrium oxide layer 2, a tin dioxide electron transport layer 3, a perovskite light absorption layer 4, a hole transport layer 5 and a top electrode 6. The specific preparation method is as follows: 1. Cleaning: In the experiment, the conductive glass substrate must be cleaned and dried first. Clean the conductive glass of appropriate size with a detergent, and then rinse it with deionized water. Then put it in an ultrasonic cleaner and use acetone, ethanol, and deionized water to ultrasonically clean it in sequence, and finally blow it dry with nitrogen to obtain a substrate with a clean surface required for the experiment.
[0024] 2. Preparation of yttrium oxide buffer layer: Place metal yttrium in a vacuum of 4x10 -4 The yttrium oxide layer was evaporated onto a conductive glass substrate in a Pa evaporation chamber at a rate of about 0.1 Å / s, and then placed in air for oxidation for 10 min to obtain a yttrium oxide layer with a thickness of about 1 nm.
[0025] 3. Preparation of tin dioxide transport layer: Prepare a precursor solution with a tin dioxide colloidal solution (purchased from Alfa Aesar, with a concentration of 15% aqueous solution), deionized water, and hydrogen peroxide in a volume ratio of 1:4:1; then stir at room temperature for 24 hours to obtain a tin dioxide precursor solution modified with hydrogen peroxide; spin-coat the tin dioxide precursor solution on a conductive substrate coated with yttrium oxide at a rotation speed of 4000 rpm for 30 seconds, and then place it on a hot plate at 150°C for annealing for 30 minutes. A tin dioxide film modified with hydrogen peroxide can be obtained, which serves as an electron transport layer. The thickness of the electron transport layer is about 30 nm.
[0026] 4. Preparation of perovskite light-absorbing layer: PbI2 was dissolved in a composite solvent with a volume ratio of DMF:DMSO = 9:1 at a molar concentration of 1.5 M, and stirred at 60 °C for 24 h, where DMF and DMSO represent N,Ndimethylformamide (DMF, 99.8%) and dimethyl sulfoxide (DMSO, 99.9%) respectively; the ammonium salt was dissolved in 1 mL of isopropanol (i.e., 1 mL of isopropanol contains 90 mg of FAI and 16 mg of MACl) at a certain mass ratio (FAI:MACl = 90 mg:16 mg), and stirred at room temperature for 24 h. The prepared precursor lead iodide solution was evenly spin-coated on the electron transport layer using a spinner; then annealed at 70 °C for 1 min. After the lead iodide is cooled to room temperature, the prepared ammonium salt solution is spin-coated onto the lead iodide, and then annealed at 150 ° C for 13 min in an atmosphere with a humidity of about 35%, to obtain a FAPbI3 perovskite light-absorbing layer film. The thickness of the perovskite light-absorbing layer is about 900 nm.
[0027] 5. Preparation of hole transport layer: 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) was prepared as a hole transport layer on the perovskite light absorbing layer film. The preparation method was as follows: 520 mg of lithium bis(trifluoromethylsulfonyl)imide (Li-TFSI) was first dissolved in 1 ml of acetonitrile and stirred for 3 min. Then 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) was dissolved in 1 ml of chlorobenzene. 28.8 μL of 4-tert-butylpyridine (TBP) and 17.5 μL of Li-TFSI acetonitrile solution were added and stirred at 40 °C for 24 h. The prepared solution was spin-coated on the perovskite film at a spin-coating speed of 3000 rpm and a spin-coating time of 20 s. The resulting film was the hole transport layer. The thickness of the hole transport layer was about 80 nm.
[0028] 6. Preparation of top electrode: An Au electrode is evaporated on the hole transport layer as a top electrode, and the thickness of the top electrode is about 80 nm, thereby obtaining a photovoltaic device based on a tin dioxide electron transport layer.
[0029] 7. Test: At AM1.5 G, the effective area of the active layer is 0.070025 cm 2 The battery was tested under the conditions of . The obtained photoelectric conversion efficiency parameter statistics are shown in Figure 2 The efficiency statistical distribution range of 18 devices from three batches is 24.86±0.61. Example 2
[0030] 1. Cleaning: Same as Example 1.
[0031] 2. Preparation of yttrium oxide buffer layer: Place the metal yttrium and the conductive glass substrate in a vacuum chamber with a degree of 4x10 -4 The Pa was evaporated in a Pa evaporation chamber with an evaporation rate of about 0.1 Å / s, and then placed in air for oxidation for 10 min, with a thickness of about 2 nm.
[0032] 3. Preparation of tin dioxide transport layer: same as in Example 1.
[0033] 4. Preparation of perovskite light-absorbing layer: same as in Example 1.
[0034] 5. Preparation of hole transport layer: same as in Example 1.
[0035] 6. Preparation of top electrode: same as in Example 1.
[0036] 7. Test: At AM1.5 G, the effective area of the active layer is 0.070025 cm 2The battery was tested under the conditions of . The obtained photoelectric conversion efficiency parameter statistics are shown in Figure 3 The efficiency of 18 devices from three batches is statistically distributed in a range of 25.18 ± 0.63. After 430 hours of continuous heating at 85 °C, the device can still maintain 83.7% of its initial efficiency, as shown in Figure 2. Figure 4 shown. Example 3
[0037] 1. Cleaning: Same as Example 1.
[0038] 2. Preparation of yttrium oxide buffer layer: Place the metal yttrium and the conductive glass substrate in a vacuum chamber with a degree of 4x10 -4 Pa was evaporated in a Pa evaporation chamber with an evaporation rate of about 0.1 Å / s, and then placed in air for oxidation for 10 min, with a thickness of about 3 nm.
[0039] 3. Preparation of tin dioxide transport layer: same as in Example 1.
[0040] 4. Preparation of perovskite light-absorbing layer: same as in Example 1.
[0041] 5. Preparation of hole transport layer: same as in Example 1.
[0042] 6. Preparation of top electrode: same as in Example 1.
[0043] 7. Test: At AM1.5 G, the effective area of the active layer is 0.070025 cm 2 The battery was tested under the conditions of . The obtained photoelectric conversion efficiency parameter statistics are shown in Figure 5 The efficiency statistical distribution range of 18 devices from three batches is 23.46±1.04. Comparative Example 1
[0044] The preparation method is as follows: 1. Cleaning: Same as Example 1.
[0045] 2. Preparation of electron transport layer: same as in Example 1.
[0046] 3. Preparation of perovskite light-absorbing layer: same as Example 1.
[0047] 4. Preparation of hole transport layer: same as Example 1.
[0048] 5. Preparation of top electrode: same as Example 1.
[0049] 6. Test: At AM1.5 G, the effective area of the active layer is 0.070025 cm 2 The battery was tested under the conditions of . The obtained photoelectric conversion efficiency parameter statistics are shown in Figure 6The efficiency of 18 devices from three batches is statistically distributed in the range of 22.63±0.96. After 430 hours of continuous heating at 85°C, the device maintains 72.8% of its initial efficiency, as shown in Figure 2. Figure 7 shown.
[0050] The preparation method provided by the present invention has a simple process, can effectively improve the photoelectric conversion efficiency of the device (by two percentage points), uniformity and repeatability, and reduce the production time and cost. The photovoltaic device prepared by the present invention has achieved good results in perovskite photovoltaic cells and has great application potential.
[0051] The above description is only a preferred specific implementation manner of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the scope of protection of the invention.
Claims
1. A method for preparing a photovoltaic device based on an yttrium oxide buffer layer, characterized in that: The following steps are involved: (1) Preparation of yttrium oxide buffer layer (1.1) Evaporating metal yttrium (Y) onto the FTO glass substrate under vacuum to form a metal yttrium layer; (1.2) The evaporated metal yttrium is placed in an external environment for natural oxidation to obtain an yttrium oxide buffer layer; (2) Preparation of tin dioxide transport layer (2.1) mixing a tin dioxide colloidal solution, deionized water, and hydrogen peroxide, and stirring to obtain a tin dioxide precursor solution; (2.2) Spin coating a tin dioxide precursor solution on the yttrium oxide buffer layer, and annealing to obtain a tin dioxide transport layer; (3) Preparation of perovskite light-absorbing layer film (3.1) Dissolve PbI2 in an organic solvent to obtain a PbI2 solution; (3.2) Dissolve the ammonium salt in isopropanol to obtain an ammonium salt solution; (3.3) Spin-coat the PbI2 solution on the tin dioxide transport layer, anneal to room temperature, spin-coat the ammonium salt solution on the PbI2 layer, and then anneal to obtain a perovskite light-absorbing layer film; (4) Preparation of hole transport layer (4.1) dissolving lithium bis(trifluoromethanesulfonyl)imide in acetonitrile to obtain an acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide; (4.2) Dissolve 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in chlorobenzene, add 4-tert-butylpyridine and acetonitrile solution of lithium bis(trifluoromethanesulfonate), heat and stir to react, and obtain a hole transport layer solution; (4.3) Spin coating the hole transport layer solution onto the perovskite light absorbing layer film to obtain the hole transport layer; (5) Preparation of top electrode A top electrode is evaporated on the hole transport layer.
2. The preparation method according to claim 1, characterized in that: The thickness of the metal yttrium layer in step 1.1 is 1-3 nm; the vacuum degree is 4x10 -4 Pa, and the evaporation rate is 0.1 Å / s.
3. The preparation method according to claim 1, characterized in that: The tin dioxide precursor solution in step 2.1 is obtained by stirring at room temperature for 24 hours.
4. The preparation method according to claim 1, characterized in that: In step 2.2, the spin coating speed is 4000 rpm, and the spin coating time is 30 s; the annealing temperature is 150° C., and the annealing time is 30 min.
5. The preparation method according to claim 1, characterized in that: The organic solvent in step 3.1 is a mixed solvent of DMF and DMSO, with a volume ratio of 9:1; the dissolution temperature is 70°C, and the stirring time is 24 h.
6. The preparation method according to claim 1, characterized in that: The annealing temperature of the PbI2 solution in step 3.3 is 70°C; the ammonium salt includes FAI and MACl; the spin-coated film is annealed in an atmospheric environment with a humidity of 35%, the annealing temperature is 145°C, and the annealing time is 13 min.
7. The preparation method according to claim 1, characterized in that: In the step 4.2, the dosage ratio of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, chlorobenzene, 4-tert-butylpyridine and the acetonitrile solution of lithium bistrifluoromethanesulfonate is 72.3 mg:1 mL:28.8 μL:17.5 μL; the ratio of lithium bistrifluoromethanesulfonate to acetonitrile in the acetonitrile solution of lithium bistrifluoromethanesulfonate is 520 mg:1 mL.
8. A photovoltaic device based on an yttrium oxide buffer layer, characterized in that: The invention comprises, from bottom to top, an FTO glass substrate, an yttrium oxide buffer layer, a tin dioxide transport layer, a perovskite light absorption layer film, a hole transport layer and a top electrode layer; the yttrium oxide buffer layer is prepared by the following method: evaporating metal yttrium (Y) onto the FTO glass substrate in a vacuum environment to form a metal yttrium layer; placing the evaporated metal yttrium in an external environment for natural oxidation to obtain the yttrium oxide buffer layer.
9. The photovoltaic device according to claim 8, characterized in that: The perovskite light absorbing layer film is an organic-inorganic hybrid perovskite FAPbI3.
10. Use of the photovoltaic device according to claim 8 or 9 in a solar cell.
Citation Information
Patent Citations
Perovskite-based thin film solar cell and preparation method thereof
CN109309162A
Preparation method and application of photovoltaic device based on stannic oxide transmission layer
CN112133831A
Perovskite function lamination film
JP2013168530A
Production method of yttria solution for buffer layer of substrate
JP2014240334A
Perovskite contacting passivating barrier layer for solar cells
US20190229285A1